BDNF Val66Met Positive Players Demonstrate Diffusion Tensor Imaging Consistent With Impaired Myelination Associated With High Levels of Soccer Heading: Indication of a Potential Gene-Environment Interaction Mechanism - Hunter, Liane E.; Freudenberg-Hua, Yun; Davies, Peter; Kim, Mimi; Fleysher, Roman; Stewart, Walter F.; Lipton, Richard B.; Lipton, Michael L. (Frontiers in Neurology, 2019)
The purpose of this study was to examine the potential effect modifying role of the BDNF Val66Met polymorphism on the association of soccer heading with white matter microstructure. We studied 312 players enrolled in the ongoing Einstein Soccer Study, a longitudinal study of amateur soccer player in New York City and surrounding areas. At enrollment and two years later, total heading in the prior 12 months (12-mo.) was estimated using an established self-report instrument and diffusion tensor imaging (DTI) was performed. Generalized Estimating Equations (GEE) logistic regression models were employed to test effect modification by the BDNF Val66Met polymorphism on the association between 12-mo. heading exposure and DTI. We identified a significant interaction of 12-mo heading*BDNF Val66Met genotype on the presence of low Radial Diffusivity, a DTI marker associated with myelination. Only Met (+) players demonstrated significantly reduced odds of low RD (OR (95 % CI): -2.36 (-3.53, -1.19)) associated with the highest vs. lowest quartile of 12-mo heading exposure. BDNF Val66Met (+) soccer players with long-term exposure to high levels of heading exhibit less low Radial Diffusivity, suggesting impaired re-myelination may be a substrate of the previously reported association between heading and poor functional outcomes in soccer players.